Prevalence and repercussions of stress and mental health issues on primary and middle school students: a bibliometric analysis - Sood, Ajay; Sharma, Deepti; Sharma, Manish; Dey, Rajiv (Frontiers in Psychiatry, 2024)
Objective: This study analyses the presence and reverberations of stress, anxiety and other mental health issues on primary and middle school students using bibliometric analysis. The focus of this study is to map the research landscape by statistically analysing existing literature, identifying key themes, trends and research hotspots in the domain of stress in school students. This study also presents analysis related to top contributing countries, journals, authors, citations, and collaboration networks.Method: A total of 1335 publications from 1962 to 10 th September 2023 were included in this study using databases of Web of Science, PubMed and Scopus. The steps involved in the bibliometric study included data collection, cleaning, and various analyses such as performance analysis, citation analysis and network analysis. The Biblioshiny by RStudio and Microsoft Excel were used for bibliometric analysis to see collaboration between countries and authors and to explore keyword analysis and thematic evolution.The findings show that China and USA have contributed the maximum number of publications. Frontiers in Psychology with 50 publications turns out to be the most prominent journal. The study presents the thematic evolution and the trend topics in this research domain. Some of the trend topics are stress, test anxiety, bullying, depression, cyberbullying, virtual reality, Mathematics anxiety, childhood maltreatment and self-compassion, primary school, and middle school. The paper also highlights the prominent authors and their collaboration network.Discussion-The study has highlighted the various reasons of stress and its potential repercussions on students. This information can be used to help parents, teachers and school administration to spot the most susceptible group of students who need immediate interventions to address various mental health issues. We see a gradual progress in the research areas being covered under this domain. More relevant areas of concern related to stress are being explored with time. With the technological advancement and the vast usage of unmonitored internet usage (especially for primary and middle school students) the stress caused by cyberbullying and peer victimization have also become important topics of research in later years.